Concurrent Mode-Division Multiplexed Half-Mode Substrate-Integrated Waveguide Link With Three Independent Data Channels - Mohamed Elsawaf; Constantine Sideris (IEEE Journal of Microwaves)
This article introduces a three-channel half-mode substrate-integrated waveguide (HMSIW) link. The link achieves three independent channels by stacking two HMSIWs vertically, with one of them utilizing both the fundamental and the first higher-order modes ( $TE_{0.50}$ and $TE_{1.50}$ ). Methods for selective excitation of both modes with good overall cross-modal isolation are introduced and presented. Furthermore, real-time eye-diagram measurements of the link using a pseudo-random binary sequence (PRBS) and on-off keying (OOK) modulation are presented in addition to a full MATLAB simulation model of the link showing its performance under quadrature amplitude modulation (QAM). The measured 10-dB return loss (RL) BW of the channels are more than 4 GHz (12–16 GHz) for the $TE_{0.50}$ modes along the two HMSIWs, and 3.6 GHz of the first higher-order mode $TE_{1.50}$ (12.1–15.7 GHz), corresponding to a concurrent bandwidth of 3.6 GHz with more than 15 dB of isolation between the channels. To the best of our knowledge, this is the first demonstration of a three-channel link using HMSIWs. The structure is fabricated and measurements agree well with the electromagnetic simulations.